Beispiel Nr: 05
$ \text{Gegeben:}\\\text{Breite} \qquad b \qquad [m] \\ \text{Umfang} \qquad U \qquad [m] \\ \\ \text{Gesucht:} \\\text{Länge} \qquad a \qquad [m] \\ \\ a = \frac{U - 2\cdot b}{ 2}\\ \textbf{Gegeben:} \\ b=1m \qquad U=19m \qquad \\ \\ \textbf{Rechnung:} \\ a = \frac{U - 2\cdot b}{ 2} \\ b=1m\\ U=19m\\ a = \frac{19m - 2\cdot 1m}{ 2}\\\\a=8\frac{1}{2}m \\\\\\ \tiny \begin{array}{|l|} \hline b=\\ \hline 1 m \\ \hline 10 dm \\ \hline 100 cm \\ \hline 10^{3} mm \\ \hline 10^{6} \mu m \\ \hline 0,001 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline U=\\ \hline 19 m \\ \hline 190 dm \\ \hline 1,9\cdot 10^{3} cm \\ \hline 1,9\cdot 10^{4} mm \\ \hline 1,9\cdot 10^{7} \mu m \\ \hline 0,019 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline a=\\ \hline 8,5 m \\ \hline 85 dm \\ \hline 850 cm \\ \hline 8,5\cdot 10^{3} mm \\ \hline 8,5\cdot 10^{6} \mu m \\ \hline 0,0085 km \\ \hline \end{array}$